Smallholder Farmers and Collective Action: What Determines the Intensity of Participation? - Elisabeth Fischer; Matin Qaim (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2011)
Collective action has become an important strategy for smallholders in developing countries to remain competitive in rapidly changing markets. However, within farmer groups, the commitment of individual members can vary, as the expected net benefits are not the same for all individuals, and opportunities to free-ride exist. Since the benefits of collective action emerge primarily through the exploitation of economies of scale, low participation rates in joint activities may put a serious threat to the success and viability of farmer groups. This article investigates determinants of smallholder participation intensity and free-riding, using the example of banana groups in Kenya. The results suggest that family labor availability and previous benefits that members received through the groups positively influence their intensity of participation in group meetings and collective marketing. Free-riding can mostly be attributed to structural and institutional conditions, such as group size and the timing of payments. More diversified farmers are less likely to sell collectively. Since smallholders are often highly diversified in their agricultural activities, farmer groups should also diversify, focusing on more than a single crop. Further policy implications are discussed.
Keywords: 330; collective action; participation intensity; smallholder farmers; Kenya